ANALISIS WACANA SARA MILLS DALAM FILM ANIMASI ISLAM “HIJRAH NISA” (ANALISIS AKUN YOUTUBE CISFORM UIN SUNAN KALIJAGA) - Kurniawati, Erna (Komodifikasi, 2019)
The meaning and understanding of Hijrah is still a human problem in today's era, many who support hijrah are struggles and battles in the way of Allah by taking up arms, but on the other hand there are also those who improve hijrah is a place to move from place to place and there is also another meaning often pronounced is hijrah is an action to go away. On the other hand, the meaning of emigration is often equated with jihad in the sense of taking up arms to preach or spread the religion of Islam, the compilation of preaching objectives is not appropriate by trying and teaching. Islamic animated film "Hijrah Nisa" comes with a new discourse that tries to be implanted about the meaning of a hijrah. Then for the formulation of the problem in this study is what is the position of the subject and object taken in this film? It is certain to answer from the formulation of this problem, namely by using Sara Mills' discourse analysis. Based on the analysis of the data presented by the youtube CISFrom UIN Sunan Kalijaga media, it shows that this media supports to build and embed the meaning of hijrah by using terms and examples that are easily debated by viewers, using migration from negative gadget and internet addiction that is used by comments from each other Blaming, blaspheming people on SOSMED and debating coaches with unknown people, switching to reducing the activities of holding gadgets and doing I'tikaf in mosques. This of course can lead the conversation to mean that hijrah does not have to be carried out in a radical way and does an attack, taking up arms like understanding what has been done a lot on the mindset of the audience. Although this subtitle film does not at all present a Nisa party to be a subject (storyteller), but the plot and journey regarding Nisa's migration is represented by another subject (Pak 'Ust) as the storyteller.